ANALISIS KINERJA KEUANGAN DENGAN DU PONT SYSTEM DAN ARUS KAS - Yeni Melia; Mirawati Mirawati; Muhammad Deni Putra (IAIN BATUSANGKAR, 2021)
The assets of PT Martina Berto Tbk always increase every year. Despite an increase in assets, the company's net profit has decreased every year, even suffered a loss in 2015. While cash and cash equivalents produced have always decreased every year. The research objective was to find out and assess the company's financial performance seen from Du Pont System and cash flow analysis. This type of research is descriptive with a quantitative approach. The financial performance of PT Martina Berto, which is produced from the Du Pont System method of 4 ratios, namely total assets turnover, net profit margin and return on equity and return on assets can be said to be less good because there has been a decline in the last 3 years from 2014-2016, whereas if see the cash flow statement, the performance produced is also less good because all the measured ratios always decrease every year.